Who Cleans the Plate? Quantity and Type of Food Waste in 78 Primary Schools’ Canteens in Italy - Falasconi, Luca; Boschini, Matteo; Giordano, Claudia; Cicatiello, Clara; Alboni, Fabrizio; Nassivera, Federico; Troiano, Stefania; Marangon, Francesco; Segrè, Andrea; Franco, Silvio (MDPI, 2025)
In advanced economies, most food waste occurs at the downstream stages of the supply chain; within the EU, it has been estimated that 64.57% of food waste occurs at the consumption stage, with about 5.4 million tons (9.45% of the total) being generated in food service. This study aims to contribute to this stream of research by providing evidence about the quantity of food waste produced in Italian primary schools and discussing the results against the evidence available in other EU countries. This research is based on a large-scale study involving 78 primary schools and over 11,000 students for a total number of almost 110,000 monitored meals. The results show that the amount of food not consumed at lunch is 21.7% of the food prepared every day. Plate waste accounts for almost 90 g/day per capita and the total amount of wasted food, including unserved food, accounts for 117 g/day per capita. To our knowledge, this study represents the largest sample size monitored in Italy under the framework of the EC Delegated Decision (EU) 2019/1597 on food waste measurement. Given its scale and adherence to the EU’s standardized methodology, this dataset should serve as the reference data for Italy reported to Eurostat, as it is based on direct measurements rather than estimates or secondary data sources. This underscores the importance of systematic, comparable data collection for tracking progress on food waste reduction at both national and European levels.
Keywords: food waste; school canteens; plate waste; food service; citizen science; public procurement